The antagonism of HIV-1 Nef to SERINC5 particle infectivity restriction involves the counteraction of virion-associated pools of the restriction factor - Trautz, Birthe; Pierini, Virginia; Wombacher, Rebecka; Stolp-Rastätter, Bettina; Chase, Amanda; Fackler, Oliver Till (Journal of virology, 2016)
SERINC3 (serine incorporator 3) and SERINC5 are recently identified host cell inhibitors of HIV-1 particle infectivity that are counteracted by the viral pathogenesis factor Nef. Here we confirm that HIV-1 Nef, but not HIV-1 Vpu, antagonizes the particle infectivity restriction of SERINC5. SERINC5 antagonism occurred in parallel with other Nef activities, including cell surface receptor downregulation, trans-Golgi network targeting of Lck, and inhibition of host cell actin dynamics. Interaction motifs with host cell endocytic machinery and the Nef-associated kinase complex, as well as CD4 cytoplasmic tail/HIV-1 protease, were identified as essential Nef determinants for SERINC5 antagonism. Characterization of antagonism-deficient Nef mutants revealed that counteraction of SERINC5 occurs in the absence of retargeting of the restriction factor to intracellular compartments and reduction of SERINC5 cell surface density is insufficient for antagonism. Consistent with virion incorporation of SERINC5 being a prerequisite for its antiviral activity, the infectivity of HIV-1 particles produced in the absence of a SERINC5 antagonist decreased with increasing amounts of virion SERINC5. At low levels of SERINC5 expression, enhancement of virion infectivity by Nef was associated with reduced virion incorporation of SERINC5 and antagonism-defective Nef mutants failed to exclude SERINC5 from virions. However, at elevated levels of SERINC5 expression, Nef maintained infectious HIV particles, despite significant virion incorporation of the restriction factor. These results suggest that in addition to virion exclusion, Nef employs a cryptic mechanism to antagonize virion-associated SERINC5. The involvement of common determinants suggests that the antagonism of Nef to SERINC5 and the downregulation of cell surface CD4 by Nef involve related molecular mechanisms., IMPORTANCE HIV-1 Nef critically determines virus spread and disease progression in infected individuals by incompletely defined mechanisms. SERINC3 and SERINC5 were recently identified as potent inhibitors of HIV particle infectivity whose antiviral activity is antagonized by HIV-1 Nef. To address the mechanism of SERINC5 antagonism, we identified four molecular determinants of Nef antagonism that are all linked to the mechanism by which Nef downregulates cell surface CD4. Functional characterization of these mutants revealed that endosomal targeting and cell surface downregulation of SERINC5 are dispensable and insufficient for antagonism, respectively. In contrast, virion exclusion and antagonism of SERINC5 were correlated; however, Nef was also able to enhance the infectivity of virions that incorporated robust levels of SERINC5. These results suggest that the antagonism of HIV-1 Nef to SERINC5 restriction of virion infectivity is mediated by a dual mechanism that is related to CD4 downregulation.